Production Performance of Murrah Buffaloes under Weaning and Suckling System of Calf Management - Solanki, C. P. S.; Lakhani, G. P.; Roy, B.; Mishra, A.; Joshi, S. K.; Aharwal, B. (International Journal of Bio-resource and Stress Management, 2022)
Sixteen Murrah buffalo’s dams and their calves were evaluated at Livestock Farm, Adhartal, Department of Livestock Production and Management, College of Veterinary Science & A.H., N.D.V.S.U., Jabalpur Madhya Pradesh, India during 12 months period (from 1st June, 2020 to 30th May, 2021). The objective was to study the production performance in weaning and suckling system of management and randomly assigned into two different groups as suckling (control) and weaning (experimental) based on their lactation yield and parities. The average daily milk let down time was significantly (p<0.05) lower in suckling group of buffaloes than weaning group of buffaloes (1.62±0.04 vs. 3.08±0.09 min). The mean value of daily colostrum yield for 5 days after calving was 3.95±0.23 and 4.7±0.15 kg for weaning and suckling buffalo groups respectively. Daily colostrum yield for suckling group of buffaloes was significantly (p<0.05) higher than weaning group of buffaloes. The average daily milk yield was higher in suckling group than the weaning group and its mean value was 4.83±0.23 kg for weaning and 6.14±0.21 kg for suckling group respectively. The average milking time and total milking time was significantly (p<0.05) lower in suckling group than weaning group of buffaloes (4.38±0.09 vs. 5.39±0.11 min and 6.01±0.11 vs. 8.42±0.12 min respectively). The average daily milk flow rate was significantly (p<0.05) higher in suckling group (0.84±0.01 kg min-1) than the weaning group (0.59±0.01 kg min-1). It is concluded that suckling have positive effect on production performance of Murrah buffalo.